Characterization of Vertisols Fertility Status and Their Implications on Chickpea (Cicer arietinum L.) Farming in Semi-Arid Areas of Itigi District in Tanzania - Julius Nyaombo; Amos Enock Majule (Indonesian Journal of Agricultural Research, 2022)
The study was conducted to assess biophysical and chemical properties of vertisols of Itigi District and examine their suitability for chickpea (Cicer arietinum L.) farming. Six soil composite samples were collected from top and subsoil of three selected farms used for growing chickpea and named as ITG-P1, ITG-P2 and ITG-P3. All profiles had a depth of 144 cm with heavy clay texture. pH levels varied from slight acidic to moderate alkaline, thus, favoring chickpea production. Exch. bases including Mg, K, and Na ranged from low to medium while Exch. Ca and CEC were high in all profiles, thereby, providing supportive environment for growth of chickpea. Available P was low and ranged from 0.54 to 2.10 mg/kg which was crucial for chickpea production necessitating fertilization with 30 to 80 kg of P2O5 /ha depending on the P available. The level of K varied as in ITG-P2 was adequate (>15 cmol(+)/kg) while in ITG-P1 and ITG-P3 was very low (<2 cmol(+)/kg) necessitating application of 30 kg of K2O/ha for chickpea production. Studied profiles had a slight difference in assessed characteristics, hence, the need to understand fertilizer demand for chickpea production was important.  Understanding fertility status of soils is important before investing in crop production where such information is not known.